CGRP Is Critical for Hot Flushes in Ovariectomized Mice - Wilhelms, Daniel B.; Dock, Hua; Brito, Haissa O.; Pettersson, Emma; Stojakovic, Andrea; Zajdel, Joanna; Engblom, David; Theodorsson, Elvar; Hammar, Mats L.; Spetz Holm, Anna-Clara E. (Frontiers in Pharmacology, 2019)
Hot flushes are common and troublesome symptoms of menopause. The neuropeptide calcitonin gene-related peptide (CGRP) is increased in plasma during hot flushes but it has not been clear if CGRP is causally involved in the mechanism underpinning the flushes. Here, we examined the effect of interventions with CGRP in a mouse model of hot flushes based on flush-like temperature increases triggered by forced physical activity in ovariectomized mice. Compared to normal mice, ovariectomized mice reacted with an exaggerated, flush-like, temperature increase after physical exercise. This increase was completely blocked by the non-peptide CGRP-antagonist MK-8825 (- 0.41 degrees Celsius, 95% CI: -0,83 to 0,012, p < 0.0001) at a dose that had no obvious effects on locomotor activity (50mg/kg). Further, the flush-like temperature increases were strongly attenuated in ovariectomized mice lacking αCGRP due to a genetic modification. Collectively, our findings suggest that CGRP is an important mediator of experimentally-induced hot flushes and they identify CGRP antagonists as promising treatment candidates for women and possibly also men with hot flushes.